Analysis of Amino Acids and Myofibrillar Protein Characteristics in Different Breeds and Cuts of Sheep Meat from the Southern Xinjiang Region - Wansen LIANG; Yuan YUAN; Yiming JIA; Zhe HAN; jiankang LU; Shuting LI; Xiyue NIU; Qian XU; Jie LI (Shipin gongye ke-ji)
The amino acid composition and protein characteristics of three Xinjiang lamb breeds (Duolang, Hetian, Qira Black) were systematically analyzed to compare their biochemical profiles. Hydration capacity, emulsifying activity, and gelation properties of myofibrillar proteins (MP) were investigated in muscle tissues from longissimus lumborum, cervical, and semimembranosus anatomical regions. Among the nine samples, the hind leg of Duolang sheep was found to have the highest total amino acid content. The proportion of basic essential amino acids (BEAA/TAA) in the neck meat of Hetian sheep was significantly higher than that of other samples, while the amino acid scores (AAS) for all three breeds consistently exceeded the FAO/WHO recommended values. In chemical score (CS) evaluation, methionine and cysteine were identified as the first limiting amino acids across all three breeds. All nine samples exhibited nutritional richness, with the ratio coefficient of amino acids (RCAA) for lysine (Lys), phenylalanine (Phe), and tyrosine (Tyr) exceeding 1. The hydrophobicity of MP isolated from the hind leg of Duolang sheep was found to be significantly higher than that of other samples (P<0.05), with a corresponding elevation in non-polar amino acid content. Furthermore, MP of the hind leg of Duolang sheep demonstrated superior emulsifying activity (EAI) and emulsion stability (ESI). When the gelation properties of MP from the external loin, neck, and hind leg were compared, the hind leg MP of all three breeds was identified to exhibit excellent gel quality, with the highest gel characteristics observed in Duolang sheep's hind leg MP. This study elucidated the nutritional quality and differences in myofibrillar protein characteristics of lamb from various breeds and cuts in southern Xinjiang, providing valuable insights for lamb farming and meat processing.